Mitophagy Mediates the Beige to White Transition of Human Primary Subcutaneous Adipocytes Ex Vivo - Attila Vámos; Abhirup Shaw; Klára Varga; István Csomós; Gábor Mocsár; Zoltán Balajthy; Cecília Lányi; Zsolt Bacso; Mária Szatmári-Tóth; Endre Kristóf (MDPI AG, 2022)
Brown and beige adipocytes have multilocular lipid droplets, express uncoupling protein (UCP) 1, and promote energy expenditure. In rodents, when the stimulus of browning subsides, parkin-dependent mitophagy is activated and dormant beige adipocytes persist. In humans, however, the molecular events during the beige to white transition have not been studied in detail. In this study, human primary subcutaneous abdominal preadipocytes were differentiated to beige for 14 days, then either the beige culture conditions were applied for an additional 14 days or it was replaced by a white medium. Control white adipocytes were differentiated by their specific cocktail for 28 days. Peroxisome proliferator-activated receptor γ-driven beige differentiation resulted in increased mitochondrial biogenesis, UCP1 expression, fragmentation, and respiration as compared to white. Morphology, UCP1 content, mitochondrial fragmentation, and basal respiration of the adipocytes that underwent transition, along with the induction of mitophagy, were similar to control white adipocytes. However, white converted beige adipocytes had a stronger responsiveness to dibutyril-cAMP, which mimics adrenergic stimulus, than the control white ones. Gene expression patterns showed that the removal of mitochondria in transitioning adipocytes may involve both parkin-dependent and -independent pathways. Preventing the entry of beige adipocytes into white transition can be a feasible way to maintain elevated thermogenesis and energy expenditure.